Manufacturing process influences properties of probiotic bacteria - Grześkowiak, Łukasz; Isolauri, Erika; Salminen, Seppo; Gueimonde, Miguel (British journal of nutrition, 2011)
Production and manufacturing methods and the food carrier may influence the properties of probiotic strains, and have an impact on the outcome of clinical intervention studies. The aim of the present study was to establish whether the properties of a specific probiotic strain, Lactobacillus rhamnosus GG, may differ depending on the product and source of the strain. In total, fifteen different L. rhamnosus isolates, among them fourteen labelled as L. rhamnosus GG, were isolated from specific probiotic products. The micro-organisms were phenotypically and genotypically characterised. Their adhesion properties were compared using the human intestinal mucus model, and the ability of the isolates to influence model pathogen adhesion to human colonic mucus was assessed. All L. rhamnosus isolates used were confirmed as members of the species L. rhamnosus. Except the reference strain OL, all L. rhamnosus isolates showed randomly amplified polymorphic DNA, enterobacterial repetitive intergenic consensus and pulsed-field gel electrophoresis profiles identical to that of L. rhamnosus GG (ATCC 53103). All L. rhamnosus isolates showed similar tolerance to acid and were able to bind to human colonic mucus. However, pathogen exclusion by inhibition and competition varied significantly among the different L. rhamnosus isolates and pathogens tested. The results suggest that different sources of the same probiotic may have significantly altered strain properties. This should be considered in in vivo studies on human subjects and also for quality control of probiotic products.